2006
DOI: 10.1080/02699050500488074
|View full text |Cite
|
Sign up to set email alerts
|

The overt behaviour scale (OBS): A tool for measuring challenging behaviours following ABI in community settings

Abstract: The OBS shows promise as a reliable, valid and responsive measure that can be used for the systematic assessment of challenging behaviours in community settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 30 publications
0
34
0
5
Order By: Relevance
“…The current study took an empirically derived approach to address this problem, by utilizing a standardized set of behaviors and descriptive criteria. This approach was previously developed by Kelly et al 3 After reviewing 534 referrals to a specialized tertiary acquired brain injury (ABI) behavior consultancy service, Kelly et al 3 found that 9 behavioral domains (verbal aggression, physical aggression against objects, physical acts against self, physical aggression against people, inappropriate sexual behavior, perseverative/repetitive behavior, wandering/absconding, inappropriate social behavior, lack of initiation) accounted for approximately 90% of all presentations, with each domain appearing in at least 10% of cases. Challenging behaviors such as these have profound consequences, disrupting an individual's independence, interpersonal relationships, community integration, and occupational functioning.…”
mentioning
confidence: 99%
“…The current study took an empirically derived approach to address this problem, by utilizing a standardized set of behaviors and descriptive criteria. This approach was previously developed by Kelly et al 3 After reviewing 534 referrals to a specialized tertiary acquired brain injury (ABI) behavior consultancy service, Kelly et al 3 found that 9 behavioral domains (verbal aggression, physical aggression against objects, physical acts against self, physical aggression against people, inappropriate sexual behavior, perseverative/repetitive behavior, wandering/absconding, inappropriate social behavior, lack of initiation) accounted for approximately 90% of all presentations, with each domain appearing in at least 10% of cases. Challenging behaviors such as these have profound consequences, disrupting an individual's independence, interpersonal relationships, community integration, and occupational functioning.…”
mentioning
confidence: 99%
“…The challenge, then, is for brain injury services to develop ways of supporting the person with ABI and managing their behaviours in the community, in less intensive and less restrictive settings 34,35 , taking into account family support needs.…”
Section: Introductionmentioning
confidence: 99%
“…All agreed to participate. Subsequently, these persons were evaluated by their therapist using the Overt Behavior Scale (OBS) [27], an instrument designed to assess the types and severity of challenging behaviors, to ensure their behavioral profile matched the inclusion criteria (e.g., score of 1 or higher on the Inappropriate Social Behavioral scale); only one person was not tested, due to the unavailability of that person’s therapist. Figure 1 presents the behavioral profile for the subjects with TBI-ISB.…”
Section: Methodsmentioning
confidence: 99%
“…In Part A, subjects were asked to read the scenario, which was followed by a behavior that was either socially appropriate or inappropriate, and then to indicate the extent to which they would have reacted in the same way if they had been in that situation. The inappropriate social behaviors proposed in the behavioral responses were inspired by those in the OBS scale [27]. Once constructed, the task underwent content validation for the behavioral responses with 14 healthy participants living in the community.…”
Section: Methodsmentioning
confidence: 99%